Diagnostic Accuracy of Dual-Energy CT in Detection of Acute Pulmonary Embolism: A Systematic Review and Meta-Analysis. Issue 2 (May 2021) - Abdellatif, Waleed; Ebada, Mahmoud Ahmed; Alkanj, Souad; Negida, Ahmed; Murray, Nicolas; Khosa, Faisal; Nicolaou, Savvas
Purpose: In this systematic review and meta-analysis, we aimed to investigate the accuracy of dual-energy computed tomography (DECT) in the detection of acute pulmonary embolism (PE). Methods: We searched Medline (via PubMed), EBSCO, Web of Science, Scopus, and the Cochrane Library for relevant published studies. We selected studies assessing the accuracy of DECT in the detection of PE. Quality assessment of bias and applicability was conducted using the Quality of Diagnostic Accuracy Studies-2 tool. Meta-analysis was performed to calculate mean estimates of sensitivity, specificity, positive likelihood ratio (PLR), and negative likelihood ratio (NLR). The summary receiver operating characteristic (sROC) curve was drawn to get the Cochran Q-index and the area under the curve (AUC). Results: Seven studies were included in our systematic review. Of the 182 patients included, 108 patients had PEs. The pooled analysis showed an overall sensitivity and specificity of 88.9% (95% confidence interval [CI]: 81.4%-94.1%) and 94.6% (95% CI: 86.7%-98.5%), respectively. The pooled PLR was 8.186 (95% CI: 3.726-17.986), while the pooled NLR was 0.159 (95% CI: 0.093-0.270). Cochran-Q was 0.8712, and AUC was 0.935 in the sROC curve. Conclusion: Dual-energy computed tomography shows high sensitivity, specificity, and diagnostic accuracy in the detection of acute PE. The high PLR highlights the high clinical importance of DECT as a prevalence-independent, rule-in test. Studies with a larger sample size with standardized reference tests are still needed to increase the statistical power of the study and support these findings.